2004
DOI: 10.1097/00004872-200409000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of ambulatory and office blood pressure phenotypes in Swedish families

Abstract: We conclude that ambulatory blood pressure, in particular at night, seems better than office blood pressure to capture the heritable part of blood pressure, suggesting that ambulatory blood pressure may be a more exact estimate of an individual's true blood pressure. Genetic studies using ambulatory blood pressure as the phenotype are likely to be more powerful than those using office blood pressure. The high heritability of pulse pressure ambulatory blood pressure indicates that variation in arterial stiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 22 publications
5
65
1
4
Order By: Relevance
“…An even higher heritability estimate of 0.63 was reported by a Swedish study. 11 A recent analysis of our Chinese twin data showed a heritability estimate of 0.45 (unpublished data), which is consistent with the American and African data. These results indicate that, similar to all other complex traits, the etiology of PP can be complicated due to the involvement of both genetic and environmental dissections.…”
Section: Introductionsupporting
confidence: 88%
“…An even higher heritability estimate of 0.63 was reported by a Swedish study. 11 A recent analysis of our Chinese twin data showed a heritability estimate of 0.45 (unpublished data), which is consistent with the American and African data. These results indicate that, similar to all other complex traits, the etiology of PP can be complicated due to the involvement of both genetic and environmental dissections.…”
Section: Introductionsupporting
confidence: 88%
“…Because ABP is a better predictor of target organ damage, cardiovascular morbidity and mortality than office BP, 68 it is of great interest to know whether 24-h BP will be a better phenotype than office BP to find genes for EH. To date, four twin studies 2528 and three family studies 2931 have reported heritability estimates for 24-h ABP recording. However, only three studies 25,30,31 reported the heritability estimates both for office and 24-h BP, with two family studies 30,31 observing higher heritability and one twin study observing similar heritability for 24-h BP.…”
Section: Discussionmentioning
confidence: 99%
“…To date, four twin studies 2528 and three family studies 2931 have reported heritability estimates for 24-h ABP recording. However, only three studies 25,30,31 reported the heritability estimates both for office and 24-h BP, with two family studies 30,31 observing higher heritability and one twin study observing similar heritability for 24-h BP. 25 For example, in the study by Fava et al ., 31 which included 260 siblings from 118 Swedish families, the heritability was 30% for 24-h SBP and 29% for 24-h DBP, whereas the heritability estimates for office BP were not significantly different from zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations